In vitro and in vivo evaluation of mefenamic acid and its complexes with Î²-Cyclodextrin and HP-Î²-Cyclodextrin - Derle, Deelip V; Bele, Mrudula; Kasliwal, Nikhil (Asian Journal of Pharmaceutics (AJP), 2014)
The objective of this research was to improve solubility, dissolution, and, consequently, bioavailability of mefenamic acid, a poorly water-soluble nonsteroidal anti-inflammatory drug, by complexation with Î²-Cyclodextrin and HP-Î²-Cyclodextrin. The complexes of mefenamic acid with Î²-Cyclodextrin and HP-Î²-Cyclodextrin were prepared by kneading method and were characterized and evaluated to study the effect of complexation on dissolution profiles and in vivo advantage. The complexes were characterized by Fourier transform infrared spectroscopy, X-ray diffraction, and differential scanning calorimetry studies. Phase solubility studies indicated complex formation with possible stoichiometry of 1:1 and a stability constant of 176 M-1 for Î²-Cyclodextrin and 103.8 M-1 for HP-Î²-Cyclodextrin. The characterization studies confirmed the inclusion of mefenamic acid within the nonpolar cavity of Î²-Cyclodextrin and of HP-Î²-Cyclodextrin. Remarkable improvement was observed in the in vitro drug release profiles in 0.1-N HCl and pH-6.8 phosphate buffer with all complexes. Mefenamic acid also showed improvement in the in vivo activity when administered orally to rats as compared with mefenamic acid per se.